Towards Advanced Sodium-Ion Batteries: Green, Low-Cost and High-Capacity Anode Compartment Encompassing Phosphorus/Carbon Nanocomposite as the Active Material and Aluminum as the Current Collector. Issue 8 (21st April 2020) - Quartarone, E.; Eisenmann, T.; Kuenzel, M.; Tealdi, C.; Marrani, A. G.; Brutti, S.; Callegari, D.; Passerini, S.
Abstract : Sodium-ion batteries (SIBs) are promising alternative to Lithium-ion batteries for massive stationary energy storage. To improve energy density, however, more performing active materials are needed. In order to allow sustainable scale-up, it is also mandatory to develop green products and processes. Herein, we report on anodes of phosphorus/carbon (P/C) nanocomposites prepared via High Energy Ball Milling (HEBM), a simple, powerful and easily scalable synthesis technique. The electrodes were prepared under oxygen-free atmosphere, using water as solvent, which enabled the use of aluminum (instead of copper) as current collector, implying significant cost reduction. The P/C nanocomposite obtained after 54 h HEBM resulted in excellent cycling stability, delivering very high specific capacity (2200 mAh g −1, C/20) and showing good capacity retention after 120 cycles. A careful structural analysis (XRD, FESEM-EDS, XPS), revealed that long milling times strongly increased cycling stability due to: (i) significant decrease of P particle size inside the matrix and deep composite amorphization, which alleviates the buffering dimensional issues typical of black phosphorus; (ii) presence of defects in the carbonaceous component, which allows easier Na + insertion into the anode. Our results show that P/C nanocomposites are very promising anode materials for SIBs, paving the way for further exploitation of nano-architectures in SIBs technology.